Artista, artista... sinong gustong mag-artistan - Aguilar, Mila D.; Matilac, Naneth; Tiongson, Lito (Pinoy Tok, 1989)
A community theater as practised by four groups, including KAIROS of Saint Joseph College, Quezon City and the Paraaque "Moro-moro" exponents.